The optimum isoleucine:lysine ratio in starter diets to maximize growth performance of the early-weaned pig - B W James; Robert D Goodband; Michael D Tokach; Jim L Nelssen; Joel M DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2000)
A total of 360 weanling pigs (initially 12.3 lb BW and approximately 18 d of age) was used in a 14-d growth assay to determine the optimal isoleucine:lysine ratio to maximize growth performance. The 12 experimental treatments consisted of either 1.00 or 1.26% apparent digestible lysine with isoleucine concentrations of 45, 50, 55, 60, or 65% of lysine. Two positive control diets were used with 1.10 and 1.39% apparent digestible lysine and 45% isoleucine:lysine to ensure that lysine was not the first limiting amino acid in the basal diets. The results of this experiment indicate that the optimal apparent digestible isoleucine:lysine ratio for the SEW pig is between 50 and 55% of apparent digestible lysine.; Swine Day, Manhattan, KS, November 16, 2000
Keywords: Swine day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-138-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 858; Swine; Isoleucine; Lysine; Weanling pigs